Pond Dynamics and Supraglacial-Englacial Connectivity on Debris-Covered Lirung Glacier, Nepal - Miles, Evan S.; Steiner, Jakob; Willis, Ian; Buri, Pascal; Immerzeel, Walter W.; Chesnokova, Anna; Pellicciotti, Francesca (Frontiers in Earth Science, 2017)
The hydrological systems of heavily-downwasted debris-covered glaciers differ from clean-ice glaciers due to the hummocky surface and debris mantle of such glaciers, leading to a relatively limited understanding of drainage pathways. Supraglacial ponds represent sinks within the discontinuous supraglacial drainage system, and have been documented to sporadically drain englacially. To assess pond dynamics, pond water level measurements were made on Lirung Glacier during May and October of 2013 and 2014. The four field seasons coincided with aerial, satellite, and terrestrial orthomosaic images and digital elevation models, which provided snapshots of the ponds and their surroundings. We analysed the glacier's closed surface catchments to identify surface drainage pathways and englacial drainage points, and compared this to field observations of surface discahrge. The ponded area was higher in the pre-monsoon than post-monsoon, with individual ponds filling and draining seasonally associated with the surface exposure of englacial conduit segments. We recorded four pond drainage events, all of which occurred gradually (duration of weeks), observed diurnal fluctuations indicative of varying supply and discharge, and we documented instances of interaction between distant ponds. The DEM drainage analysis identified numerous sinks >3m across the glacier surface, few of which exhibited ponds (23%), while the field survey highlighted surface discharge only explicable via englacial routes. Taken together our observations provide evidence for widespread supraglacial-englacial connectivity for meltwater drainage paths. Results suggest that progressive englacial conduit collapse events, themselves likely driven by supraglacial pond drainage, enable the glacier surface to evolve into a configuration following relict englacial conduit systems. Within this system, ponds form in depressions of reduced drainage efficiency and link the supraglacial and englacial drainage networks.